About the Math Performance in Stressful Situations - Torang Siregar; Zainuddin `` `Batubara; Risky Ardian; Awal Harahap (MultiTech Publisher, 2023)
Whether because individuals are made aware of negative stereotypes about how they should perform or are in a high-stakes testing situation, a stressful environ- ment can adverselyaffect the success people have in solving math problems. I review work examining how unwanted failure in math occurs and individual differences in those most likely to fail. This work suggests that a high-stress situation creates worries about the situation and its consequences that compete for the working memory (WM) normally available for performance. Consequently, the performance of individuals who rely most heavily on WM for successful execution (i.e., higher-WM individuals) is most likely to decline when the pressure is on.